Pengaruh Solvabilitas, Likuiditas, Profitabilitas Dan Ukuran Perusahaan Terhadap Audit Report Lag - Edo Ferdian Nugraha; Usdeldi Usdeldi; Puteri Anggi Lubis (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
The aim of this research is to determine the effect of solvency, liquidity, profitability and company size on audit report lag in companies listed on the Jakarta Islamic Index 70 on the Indonesia Stock Exchange in 2020-2022. The method used in this research is a quantitative method. This research uses secondary data in the form of annual reports of the companies sampled in the research and can be obtained from the Indonesian Stock Exchange website. Samples were taken using purposive sampling technique, totaling 14 companies. The data obtained and collected was then processed using the SPSS 27 application. The data analysis techniques used were descriptive statistics, classical assumption testing, multiple linear regression analysis, and hypothesis testing. Based on the research results, it shows that partially solvency has an effect on audit report lag, while profitability, liquidity and company size have no effect on audit report lag. Simultaneously, solvency, liquidity, profitability and company size have no effect on audit report lag.